FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMILIHAN MASKAPAI OLEH WISATAWAN DOMESTIK MILENIAL KE BALI - Darayanti, L.P.R. Prema; Sasrawan Mananda, I Gusti Putu Bagus; Dewi, L.G.L.K (Jurnal IPTA (Industri Perjalanan Wisata); Vol 9 No 1 (2021): Jurnal IPTA (July 2021), 2021)
Bali is one of the tourist destinations that is favorite by domestic tourists for a vacation. In recent years, domestic tourist visits to Bali have been dominated by the millennial generation. To be able to visit Bali, tourists can pass through land and air routes. Apart from the presence of highways along the island of Java that facilitates access to Bali, the use of airways is still in demand by domestic tourists to date because it is more efficient in travel time. This study aims to determine the factors that influence the decision of airline selection by millennial domestic tourists to Bali. The sample of this research is millennial domestic tourists to Bali using the air route. The technique of determining the sample using purposive sampling on 100 respondents. Data analysis techniques were performed, namely: validity, reliability, and factor analysis. The results of this study are: 1) Six factors influence the decision to choose an airline to Bali. 2) The dominant factor in millennial domestic tourists choosing airlines to Bali is psychological factors. This factor consists of five forming indicators, namely: (1) Value, (2) Security, (3) Image of airline brand, (4) Perception, (5) Timeliness, (6) Family trust, (7) Family loyalty to airline brands, (8) Knowledge of airlines, (9) Experience with airlines.